Time to benefit for colorectal cancer screening: survival meta-analysis of flexible sigmoidoscopy trials. (16th April 2015) - Tang, Victoria; Boscardin, W John; Stijacic-Cenzer, Irena; Lee, Sei J
Abstract : Objective To determine the time to benefit of using flexible sigmoidoscopy for colorectal cancer screening. Design Survival meta-analysis. Data sources A Cochrane Collaboration systematic review published in 2013, Medline, and Cochrane Library databases. Eligibility criteria Randomized controlled trials comparing screening flexible sigmoidoscopy with no screening. Trials with fewer than 100 flexible sigmoidoscopy screenings were excluded. Results Four studies were eligible (total n=459 814). They were similar for patients' age (50-74 years), length of follow-up (11.2-11.9 years), and relative risk for colorectal cancer related mortality (0.69-0.78 with flexible sigmoidoscopy screening). For every 1000 people screened at five and 10 years, 0.3 and 1.2 colorectal cancer related deaths, respectively, were prevented. It took 4.3 years (95% confidence interval 2.8 to 5.8) to observe an absolute risk reduction of 0.0002 (one colorectal cancer related death prevented for every 5000 flexible sigmoidoscopy screenings). It took 9.4 years (7.6 to 11.3) to observe an absolute risk reduction of 0.001 (one colorectal cancer related death prevented for every 1000 flexible sigmoidoscopy screenings). Conclusion Our findings suggest that screening flexible sigmoidoscopy is most appropriate for older adults with a life expectancy greater than approximately 10 years.